Aluminum Overload: An Easily-Ignored Problem in Dialysis Patients with Hyperparathyroidism - Kan, Wei-Chih; Chien, Chih-Chiang; Lu, Yi-Hua; Hwang, Jyh-Chang; Su, Shih-Bin; Wang, Hsien-Yi (IntechOpen, 2012)
None